Percursos do amor e do feminino na Revista Era Nova: Paraíba dos anos 1920 - Rodrigues, Alzira de Cássia da Silva (2014)
This paper intends to discuss some questions raised about love through the perspective of gender discussions, in the Era Nova magazine, circulated in Paraíba in the 1920s. We emphasized the relational field of History and Literature, notably the discursive practices of Era Nova, a magazine considered, at the time, as literary, illustrative and informative, meant for the urban middle classes. The texts we gave more attention in this work lead us to the displacement of affective relationships, especially, to the historical conditions that enable the diffusion of love as a reason for conjugal unions, as well as the association of romantic love centered on the consolidation of marriage and motherhood. We approached the intersection and influences occurred around the indications of modern, family values, gender identifications, sociability, sexual exercise and loving practices in daily life of people in the 1920s, in order to point out their social expectations.